Intraosseous carcinoma of the jaws—A clinicopathologic review. Part I: Metastatic and salivary‐type carcinomas1. Issue 6 (31st January 2012) - Woolgar, Julia A.; Triantafyllou, Asterios; Ferlito, Alfio; Devaney, Kenneth O.; Lewis, James S.; Rinaldo, Alessandra; Slootweg, Pieter J.; Barnes, Leon
Abstract This is the first part of a 3‐part comprehensive review of intraosseous carcinoma of the jaws. We have outlined 4 groups of intraosseous carcinoma of the jaws (metastatic, salivary‐type, odontogenic, and primary intraosseous carcinoma), emphasizing the need for accurate diagnosis and the problems associated with changing classification systems, standardization of diagnostic criteria and nomenclature, and the accuracy of existing literature. In this first part, the features of metastatic and the very rare salivary‐type carcinomas of the jaws are examined with particular emphasis on histologic and immunohistochemical characteristics, diagnostic difficulties, and uncertainties. © 2012 Wiley Periodicals, Inc. Head Neck, 2012